2020
DOI: 10.1002/jor.24584
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma lysate displays antibiofilm properties and restores antimicrobial activity against synovial fluid biofilms in vitro

Abstract: Infectious arthritis is difficult to treat in both human and veterinary clinical practice. Recent literature reports Staphylococcus aureus as well as other gram‐positive and gram‐negative isolates forming free‐floating biofilms in both human and equine synovial fluid that are tolerant to traditional antimicrobial therapy. Using an in vitro equine model, we investigated the ability of platelet‐rich plasma (PRP) formulations to combat synovial fluid biofilm aggregates. Synovial fluid was infected, and biofilm ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 50 publications
4
60
0
2
Order By: Relevance
“…Evolving treatments to improve outcomes in chronically infected nonhealing tissues include implant surface coatings, local antibiotic release systems, and biological therapies. [25][26][27][28][29][30][31] Mesenchymal stromal cells (MSCs) possess antimicrobial and immunomodulatory properties and are particularly attractive as adjunctive therapies to antibiotics as they are not subject to development of antimicrobial resistance. 29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] MSCs are vital participants in normal tissue repair processes, promoting healing through angiogenesis, epithelialization, collagen deposition, granulation tissue formation, and release of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Evolving treatments to improve outcomes in chronically infected nonhealing tissues include implant surface coatings, local antibiotic release systems, and biological therapies. [25][26][27][28][29][30][31] Mesenchymal stromal cells (MSCs) possess antimicrobial and immunomodulatory properties and are particularly attractive as adjunctive therapies to antibiotics as they are not subject to development of antimicrobial resistance. 29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] MSCs are vital participants in normal tissue repair processes, promoting healing through angiogenesis, epithelialization, collagen deposition, granulation tissue formation, and release of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is recognized that doses several-fold greater than MIC may be required to kill bacteria in synovial biofilms present in septic arthritis, as has been previously reported in vitro. 35 These findings provide sufficient evidence to recommend that doses for in vivo IA antibiotic administration in dogs should be further assessed for safety and efficacy at concentrations greater than MIC and at or below determined IC50 for each antibiotic.…”
Section: Discussionmentioning
confidence: 74%
“…[38][39][40] Finally, bacterial biofilms in septic arthritis, either attached to the synovial lining or free-floating in synovial fluid, may limit efficacy of IA-administered antibiotics, requiring higher doses to be used to be effective. 35 In some cases, it may not be possible to achieve bactericidal doses that are not simultaneously cytotoxic when treating biofilms, which warrants further evaluation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is conceivable that the presence of sepsis, or inflammatory mediators associated with sepsis, may alter antibiotic cytotoxicity profiles as well as drug distribution from the joint due to increased inflammation, but this was beyond the scope of the current study. The ability of bacterial pathogens to form biofilms in septic arthritis, either attached to each other free‐floating in synovial fluid or along the synovial lining, may limit efficacy of IA antibiotics, requiring higher doses 39 . The initial in vitro studies reported here were necessary to determine IC50 levels in normal joint cells and compare cytotoxicity between antibiotics to move forward with additional work that would account for other variables encountered clinically.…”
Section: Discussionmentioning
confidence: 99%